Haemoglobin value and red blood cell transfusions in prolonged weaning from mechanical ventilation: a retrospective observational study. Issue 1 (14th June 2022) - Fritsch, Sebastian Johannes; Dreher, Michael; Simon, Tim-Philipp; Marx, Gernot; Bickenbach, Johannes
Abstract : Introduction: The role of haemoglobin (Hb) value and red blood cell (RBC) transfusions in prolonged weaning from mechanical ventilation (MV) is still controversial. Pathophysiological considerations recommend a not too restrictive transfusion strategy, whereas adverse effects of transfusions are reported. We aimed to investigate the association between Hb value, RBC transfusion and clinical outcome of patients undergoing prolonged weaning from MV. Methods: We performed a retrospective, single-centred, observational study including patients being transferred to a specialised weaning unit. Data on demographic characteristics, comorbidities, current and past medical history and the current course of treatment were collected. Weaning failure and mortality were chosen as primary and secondary endpoint, respectively. Differences between transfused and non-transfused patients were analysed. To evaluate the impact of different risk factors including Hb value and RBC transfusion on clinical outcome, a multivariate logistic regression analysis was used. Results: 184 patients from a specialised weaning unit were analysed, of whom 36 (19.6%) failed to be weaned successfully. In-hospital mortality was 18.5%. 90 patients (48.9%) required RBC transfusion during the weaning process, showing a significantly lower Hb value (g/L) (86.3±5.3) than the non-transfusion group (95.8±10.5). In the multivariate regression analysis (OR 3.24; p=0.045), RBC transfusion was associated with weaning failure. However, the transfusion group had characteristics indicating that these patients were still in a more critical state of disease. Conclusions: In our analysis, the need for RBC transfusion was independently associated with weaning failure. However, it is unclear whether the transfusion itself should be considered an independent risk factor or an additional symptom of a persistent critical patient condition.